Employ of Public Relations in Building Awareness of Security against Terrorism A Survey of the Employees of the Directorate General of Public Relations and Media at the Ministry of Interior - عبد الغني, ليث عبد اللطيف; جاسم, باقر موسى (ALBAHITH ALALAMI, 2017)
This study aims at identifying the role played by Public Relations in the field of security awareness of the dangers of terrorism. The research is directed to the employees at the Directorate General of Public Relations and Media at the Ministry of Interior. And that on the basis that those who play an important role in the security awareness are the security institutions, primarily the Ministry of Interior, since this Directorate is responsible for all subjects related to the public security using public relations science. It aims at identifying the functions, methods and communication tools used by the Directorate to raise awareness about the dangers of terrorism. In order to achieve the research objectives, the researcher uses the survey method based on the questionnaire as a research tool. The researcher designs a questionnaire based on the theoretical framework of the research. The resolution consists of four axes: axes of personal data, axes of public relations objectives in security institutions, the focus of public relations functions in raising awareness of the dangers of terrorism and the focus of security of awareness of the dangers of terrorism in public relations.